PENGARUH PENERAPAN PENDEKATAN PEMBELAJARAN SCAFFOLDINGTERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 15 PALEMBANG - Putri Fadilah; Dewi oryati; Djumadiono Djumadiono (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
This study aims to determine whether there is a difference in the effect of applying scaffolding approach (scaffolding) with a teacher-centered learning approach to student learning motivation on economic subjects in SMA Negeri 15 Palembang. Hypothesis of thisresearch is There is difference of influence of applying of scaffolding approach (scaffolding) with teacher-centered approach to student's learning motivation on economic subject at SMA Negeri 15 Palembang. Population in this research is all of student of X class of even semester at SMA Negeri 15 Palembang in academic year 2011/2012 with 363 people, while the sample is class X.8 and X.9 which is 82 people. The sample is obtained by using cluster sampling technique which after drawing got class X.8 as experiment class counted 41 student and class X.9 as control class counted 41 student. Data collection techniques used were questionnaires and observations. Questionnaires are used to determine students' attitudes after applying scaffolding learning approaches and after applying teacher-centered approaches. Observation is used to determine the level of student activeness during the learning process takes place in the classroom. Data analysis techniques used with the t-test formula previously performed normality test and homogeneity test data. Based on data analysis, t = 19,62 and ttable = 1,993 thus Ha proposed accepted that there is difference of influence of applying scaffolding approach (scaffolding) with teacher-centered learning approach to student's learning motivation on economics subject at SMA Negeri 15 Palembang.